Case report: Olaparib as an experimental therapy in a BRCA2-mutated patient with metastatic ovarian adenocarcinoma that originated from liver cancer - Li, Caixia; Ye, Wenlei; Zhou, Wenni; Ye, Zhikang; Yang, Weihong; Cheng, Zhongping (Frontiers in Oncology, 2022)
Secondary ovarian tumor (STO) is not a frequent disease. To date, there is still a lack of standard treatment for STO due to the relative heterogeneity. Liver cancer metastasis to the ovary is extremely rare with only 17 living cases having been reported so far, making it impossible to launch large-scale prospective studies and formulate the standard intervention for the patients. We herein report a rare case of STO with liver primary cancer metastasis to the ovary and omentum in a 66-year-old woman. The patient underwent a debulking surgery with the removal of the uterus, bilateral fallopian tubes, bilateral ovaries, appendix and a large part of the omentum majus. The next-generation sequencing was conducted after the operation, identifying BRCA2 mutation. Because strongly refusing chemotherapy, she received olaparib as an experimental therapy. After the administration of surgery and olaparib, the serum value of CA125 and AFP decreased dramatically and basically maintained within normal range. So far, she has achieved nearly 2-year survival and lives a relatively normal life with good quality.